Ibn Thufail's Philosophical Thoughts - Maryana Sepiana; Maspuroh; Julpiah Apipah; Fikri Algipar (Penerbit Hellow Pustaka, 2025)
Ibn Thufail, a 12th-century Islamic philosopher and intellectual, made significant contributions to the tradition of philosophical thought, especially in relation to rationalism, metaphysics, and the relationship between religion and philosophy. His greatest work, Hayy bin Yaqzan, describes the intellectual journey of a man who finds knowledge and understanding of God through rational observation and reflection, without the aid of revelation or external authority. Ibn Thufail's thought reflects an attempt to bridge the world of Greek philosophy with the tradition of Islamic thought, as well as providing insight into the relationship between reason and revelation. This article analyzes the main ideas in Ibn Thufail's thought, including the concept of creation, human existence, and the search for ultimate truth. Through a critical examination of Hayy bin Yaqzan, this paper aims to explore the relevance of Ibn Thufail's thought in the context of contemporary philosophical thought and its contribution to the development of Islamic philosophy.